Moj pogled na osamosvajanje slovenskega športa 1988–1992 - Šugman, Rajko (Šport (Ljubljana), 2021)
The contribution about the gaining of independence by Slovenian sport between 1988 and 1992 was written by Rajko Šugman, one of the people actively involved in the independence process, based on primary and secondary sources and his own notes. In the mentioned period he was a member of the presidency of the Association of Physical Culture Organisations of Yugoslavia (ZTKJ), a member of the presidency of Sport Association of Slovenia and, since 1990, its president. In 1999 he wrote the book “A Landmark Period of Slovenian Sport 1988–1994”, published by the Faculty of Sport of the University of Ljubljana. It has 172 pages, 155 quoted sources, 46 other sources – books and articles. It includes two reviews by university teachers, a historian and a political scientist. Moreover, during the mentioned period, Šugman attended all the meetings of the presidency of the ZTKJ as well as all joint meetings of the presidency of the ZTKJ and the Yugoslav Olympic Committee (JOC), where he took an active part. Ivo Zorčič was also a member of the presidency of the ZTKJ, whereas Janez Kocijančič and Miha Ravnik were members of the presidency of JOK. The presidency of the ZTKJ and JOK also included other Slovenians who were elected by the Yugoslav Expert Associations (JZS) and also had voting rights.
Keywords: history; olimpizem; Olympism; osamosvojitev Slovenije; Slovenia; Slovenija; sport; šport; zgodovina